A functional variant at the miR‐885‐5p binding site of CASP3 confers risk of both index and second primary malignancies in patients with head and neck cancer. Issue 4 (27th December 2012) - Guan, Xiaoxiang; Liu, Zhensheng; Liu, Hongliang; Yu, Hongping; Wang, Li‐E; Sturgis, Erich M.; Li, Guojun; Wei, Qingyi
Abstract : Caspases are important regulators and executioners in the apoptosis pathways and play crucial roles in carcinogenesis. We tested the hypothesis that functional variants of CASP genes are associated with risk of squamous cell carcinoma of the head and neck (SCCHN) and second primary malignancy (SPM). We genotyped 7 selected, potentially functional single nucleotide polymorphisms (SNPs) located in the microRNA binding sites of the 3′ untranslational region (UTR; 2 in CASP3, 1 in CASP6, and 4 in CASP7 ) and evaluated their associations first with risk of SCCHN in 1066 patients with SCCHN and 1074 cancer‐free control subjects and then with SPM in 846 patients in the same non‐Hispanic white study population. We found that compared with the CASP3 TT genotype of rs1049253, the variant TC/CC genotypes were associated with significantly increased risk of SCCHN (adjusted odds ratio = 1.29 and 95% confidence interval 1.07‐1.56) and SPM (adjusted hazard ratio = 1.79 and 95% CI=1.02–3.16) and worse SPM‐free survival (log‐rank P = 0.020), but no associations were found for the other 6 SNPs. We then performed additional experiments to seek functional relevance of the rs1049253 SNP. First, the luciferase activity and miR‐885‐5p mimic transfection tests suggested that CASP3 was the target of miR‐885‐5p and that rs1049253T>C resulted in altered regulation of the CASP3 expression. Second, the rs1049253 CC genotype was associated with reduced levels of CASP3 mRNA in peripheral blood mononuclear cells from 118 SCCHN patients and 103 cancer‐free control subjects and lower levels of CASP3 protein expression in 11 head and neck cancer cell lines, compared with the TT genotype. Taken together, our data suggest that the miR‐885‐5p binding site rs1049253T>C SNP in the 3′‐UTR of CASP3 modulates CASP3 expression at both mRNA and protein levels and thus contributes to SCCHN susceptibility.—Guan, X., Liu, Z., Liu, H., Yu, H., Wang, L.‐E., Sturgis, E. M., Li, G., and Wei, Q. A functional variant at the miR‐885‐5p binding site of CASP3 confers risk of both index and second primary malignancies in patients with head and neck cancer. FASEB J. 27, 1404–1412 (2013). www.fasebj.org